A simplified and easy‐to‐use HIP HOP assay provides insights into chalcone antifungal mechanisms of action. Issue 23 (9th September 2022) - Prescott, Thomas A. K.; Anaissi‐Afonso, Laura; Fox, Keith R.; Maxwell, Anthony; Panaretou, Barry; Machín, Félix
Abstract : Elucidating the mechanism of action of an antifungal or cytotoxic compound is a time‐consuming process. Yeast chemogenomic profiling provides a compelling solution to the problem but is experimentally complex. Here, we demonstrate the use of a highly simplified yeast chemical genetic assay comprising just 89 yeast deletion strains, each diagnostic for a specific mechanism of action. We use the assay to investigate the mechanism of action of two antifungal chalcone compounds, trans ‐chalcone and 4′‐hydroxychalcone, and narrow down the mechanism to transcriptional stress. Crucially, the assay eliminates mechanisms of action such as topoisomerase I inhibition and membrane disruption that have been suggested for related chalcone compounds. We propose this simplified assay as a useful tool to rapidly identify common off‐target mechanisms. Abstract : Here, we demonstrate a simplified HIP HOP assay comprising 89 yeast deletion strains, each diagnostic for common cell inhibitory mechanisms of action. We test two chalcone compounds with unknown mechanisms, trans ‐chalcone and 4′‐hydroxychalcone and show that both act through transcriptional stress. The assay is both easy and cheap to use and can help identify and eliminate common mechanisms of action.